Analisis Pengelolaan Sarana Prasarana Kantor Dalam Meningkatkan Produktivitas Kerja Pegawai Di PT. Artajasa Pembayaran Elektronis - Irfan , Andri; Firdaus , Adhy; Prayitno , Sugeng (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2024)
This research is a qualitative research with a descriptive analytical approach, which is a research method used to obtain in-depth data, a data that contains meaning and can significantly affect the substance of the research. Qualitative research methods are based on philosophy, used to study scientific (experimental) conditions in which the researcher is the instrument. The data collection technique is carried out by exploring the research subject through observation, interview, and recording procedures using data sources. Data analysis is carried out through the stages of data reduction, data presentation and drawing conclusions or verification. The purpose of this study is to systematically describe the focus of research related to the process of managing office infrastructure facilities in increasing employee work productivity at PT. Electronic Payment Artajasa in Serpong, South Tangerang. The results of the study show that in general, the process of managing office infrastructure facilities has been carried out well so that it is able to increase work productivity, but this condition has not been maximized due to the limited space capacity that occurs, including the availability of parking spaces and meeting rooms. In addition, employees also tend to pay less attention to the rules made related to occupational health and safety so that this indifference becomes a habit or habit of employees that can cause the risk of work accidents.